Red de Sensores Inalámbricos para la Adquisición de Datos en Casas de Cultivo - Madruga Peláez, Alexandra; Estevez Pérez, Abel Alejandro; López, Richar Sosa; Santana Ching, Iván; García Algora, Carlos Manuel (Ingeniería, 2019)
Context: The acquisition and storage of environmental parameters, through wireless sensor networks, makes it possible to analyze the growth and development of protected crops. This analysis in agriculture impose challenges because are living organisms and where it is not possible to control all the variables. Method: A hardware and software architecture is designed using a wireless sensor network for acquisition of data in greenhouses. The simulations are carried out in the UEB of Various Crops “Valley of the Yabu” of Santa Clara for two hours with six measurement nodes, a coordinator and gateway. An energetic analysis of the proposal was made calculating the real life time of batteries. Results: The experiments demonstrate the effectiveness of the design, storing all the measurements transmitted from different places inside the greenhouses. The energetic analysis guarantees high durability of the batteries of the measurement nodes. Conclusions: With the acquisition system exposed, the values of the effective variables could be maintained or modified for reducing losses of resources and improving productive efficiency.